Thiopyrano[2, 3-d]thiazole structures as promising scaffold with anticancer potential. (1st December 2022) - Finiuk, Nataliya; Zelisko, Nataliya; Klyuchivska, Olga; Yushyn, Ihor; Lozynskyi, Andrii; Cherniienko, Alina; Manko, Nazar; Senkiv, Juliya; Stoika, Rostyslav; Lesyk, Roman
Abstract: Seven chromeno[4′, 3':4, 5]thiopyrano[2, 3- d ]thiazole derivatives were synthesized and screened for their cytotoxic effects on different lines of mammalian leukemia, breast adenocarcinoma, glioblastoma, and pseudo-normal and normal cells. The derivative 3 demonstrated toxicity towards tumor cells of Jurkat, K562, U251, HL-60, MCF-7, and MDA-MB-231 lines. At the same time, this compound possessed low toxicity (IC50 > 100 μM) towards cells, used as control, representing non-tumor, somatic cells: HaCaT, HEK293 cells as well as murine Balb/c 3T3 and J774.2 cells, mink Mv1Lu cells, and normal mitogen-activated human blood lymphocytes. The derivative 3 induced apoptosis in human leukemia Jurkat T-cells and glioblastoma U251 cells via mitochondria-dependent pathway and inhibition of the DNA reparation enzyme PARP-1. This compound triggered pro-apoptotic morphological changes in Jurkat and U251 cells, namely chromatin condensation, nuclei fragmentation, and membrane blebbing. However, the DNA damaging effects of compound 3 were significantly lower in normal human lymphocytes, compared with such results in tumor Jurkat and U251 cells. The DNA damaging effects of compound 3 were unrelated to its DNA-binding and/or DNA-intercalating abilities. This compound induced the accumulation of endogenous reactive oxygen species (ROS), namely superoxide radicals, in human leukemia and glioblastoma cells. Our finding indicated that compound 3 inhibited the viability of human leukemia T-cells and glioblastoma cells via induction of DNA damage and apoptosis through ROS-mediated mitochondrial pathway. Graphical abstract: Image 1 Highlights: Synthesis of novel antineoplastic chromeno[4′, 3':4, 5]thiopyrano[2, 3- d ]thiazoles. Compound 3 possesses highest toxicity towards human leukemia T-cells. Pseudo-normal cells and normal lymphocytes are resistant to action of compound 3. Compound 3 induces ROS production and apoptosis in leukemia and glioblastoma cells. DNA damage enhanced by compound 3 in tumor cells correlates with PARP-1 inhibition.